Pengaruh Latar Belakang Pendidikan Guru terhadap Kompetensi Pedagogik dan Hasil Belajar Matematika Siswa - Maula, Nihlah Ni’matul; Nalim (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
This research aims to investigate the pedagogical competency outcomes of teachers with backgrounds in mathematics education versus those without, to examine the mathematics learning outcomes of students taught by teachers with backgrounds in mathematics education versus those without, and to analyze the influence of teachers' pedagogical competency on students' mathematics learning achievement. The analytical method employed in this study is the independent sample t-test followed by simple linear regression. The findings reveal that the pedagogical competency scores of teachers with backgrounds in mathematics education (62.86) are significantly higher than those of teachers without such backgrounds (58.16). Similarly, the mathematics learning outcomes of students taught by teachers with backgrounds in mathematics education (71.84) are significantly higher than those of students taught by teachers without backgrounds in mathematics education (60.03). There is also a significant influence of teachers' pedagogical competency on students' mathematics learning outcomes, with a coefficient of determination (R square) value of 9.9% from the linear regression analysis.